Researching the Paranormal: How to Find Reliable Information about Parapsychology, Ghosts, Astrology, Cryptozoology, Near-Death Experiences, and More - Block, Courtney M. (Rowman & Littlefield Publishers, 2020)
The paranormal has long been a hotly contested topic, especially in academia. Most people are entertained by the paranormal or casually read a few books they come across on the topic, perhaps assuming that these topics are nothing more than campfire fodder. Of course, there’s nothing wrong with being entertained by the paranormal, but how many people know that there is a long history of academic, scientific, and credible research into topics such as extrasensory perception, hauntings, poltergeists, cryptozoological sightings, near-death experiences, and more? In Researching the Paranormal, Courtney M. Block provides an overview of paranormal research and introduces readers to an assortment of resources that seriously examine various paranormal topics. She shows readers how to think critically about paranormal sources and how to apply the components of credibility when conducting their own paranormal investigations. Highlighting the long history of serious, academic inquiry into various paranormal topics, Block provides citations to primary source documents, journal articles, helpful databases, encyclopedias, dictionaries, and books. In addition, she provides a historical overview of various paranormal phenomena such as parapsychology, cryptozoology, ufology, divination, ghosts, hauntings, and more.